Testing Social Media Marketing Activities on Continuance Intention: The Role of Brand Image and E-Wallet User Satisfaction as Mediating Variables - Kersita, Nicken Dj; Sarmigi, Elex; Nilda, Elvi (KINERJA, 2026)
This research aims to determine the influence of social media marketing on continuance intention, both directly and through the mediating effects of brand image and user satisfaction. This research employs a quantitative approach, collecting primary data via a Google Forms questionnaire. The Research population involved e-wallet users, with a sample of 75 respondents. The collected data were then analyzed using Structural Equation Modeling (SEM) with SmartPLS. This research indicates that social media marketing (SMM) and brand image do not directly influence continuance intention. Meanwhile, SMM directly influences brand image and user satisfaction. User satisfaction has a direct effect on continuance intention. Meanwhile, SMM, which is mediated by brand image, does not affect continuance intention. Moreover, SMM, which is mediated by user satisfaction, affects continuance intention. Likewise, SMM, which is mediated by user satisfaction, influences continuance intention. Additionally, SMM affects user satisfaction through the mediation of brand image. Brand image, mediated by user satisfaction, also influences the intention to continue using the service (continuance intention).